Improvement of left ventricular filling and pulmonary artery pressure following unilateral renal artery total occlusion stenting in a patient with recurrent congestive heart failure complicated by renovascular hypertension and renal failure. (20th October 2015) - Kawarada, Osami; Kitajima, Ryota; Sugano, Yasuo; Noguchi, Teruo; Anzai, Toshihisa; Ogawa, Hisao; Yasuda, Satoshi
Abstract: Recurrent congestive heart failure related to renal artery disease is an important clinical entity that is typically observed in bilateral renal artery stenosis or solitary functioning kidney. However, the relationship between heart failure and unilateral renal artery disease, especially that with total occlusion, remains unclear. We report a successful management by unilateral renal artery total occlusion stenting with an evidence of improvement of left ventricular filling and pulmonary artery pressure in case of a patient suffering from medical therapy resistant recurrent congestive heart failure with preserved ejection fraction.